LEXICAL RELATIONS IN KELLY CLARKSON™S SONGS - Guntar, Muhammad . (LINGUISTIK TERAPAN, 2023)
This study is about analysis of lexical relations in Kelly Clarkson™s songs. The aim of this study is to find out types of lexical relations by Saeed™s theory that have been found in Kelly Clarkson™s songs and which most dominant lexical relations found in Kelly Clarkson™s songs. This study emerges from the qualitative research. The writer used several Kelly Clarkson™s songs namely Piece by Piece, Breakaway, Dark Side and Miss Independent as the data sources. The finding of this study is categorized by Saeed™s theory namely homonym, polysemy, synonymy, antonym, hyponymy, and meronymy. The results of the study found out synonymy, antonymy, polysemy, homonymy, hyponymy, and meronymy in Kelly Clarkson™s songs. The most dominant lexical relations found in those songs is polysemy. It was found 7 cases from 20 cases in total. Polysemy is a less well-known term than synonym or antonym, although it relates to a far more significant sense relationship. In one word, it can describe two or more meanings.